2020
DOI: 10.3389/fnana.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Molecules Related to Neurotransmission in the Nervous System of the Mussel Crenomytilus grayanus

Abstract: In bivalves neurotransmitters are involved in a variety of behaviors, but their diversity and distribution in the nervous system of these organisms remains somewhat unclear. Here, we first examined immunohistochemically the distributions of neurons containing different neurotransmitters, neuropeptides, and related enzymes, as well as the proliferative status of neurons in the ganglia of the mussel Crenomytilus grayanus. H-Phe-Met-Arg-Phe-NH2 (FMRFamide), choline acetyltransferase (ChAT), γaminobutyric acid (GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…The preadsorption of the diluted antiserum with 10 mg/ml BSA overnight at 4°C did not influence this staining, i.e., these antibodies recognized only serotonin and not BSA. Data from other groups have shown that these antibodies detect serotonin in adult bivalves and their planktotrophic larvae ( Voronezhskaya et al, 2008 ; Dyachuk and Odintsova, 2009 ; Dyachuk et al, 2015 ; Battonyai et al, 2018 ; Pavlicek et al, 2018 ; Yurchenko et al, 2019 ; Kotsyuba et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preadsorption of the diluted antiserum with 10 mg/ml BSA overnight at 4°C did not influence this staining, i.e., these antibodies recognized only serotonin and not BSA. Data from other groups have shown that these antibodies detect serotonin in adult bivalves and their planktotrophic larvae ( Voronezhskaya et al, 2008 ; Dyachuk and Odintsova, 2009 ; Dyachuk et al, 2015 ; Battonyai et al, 2018 ; Pavlicek et al, 2018 ; Yurchenko et al, 2019 ; Kotsyuba et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to serotonin antibodies, we used an FMRFamide antibody to detect nervous system elements in the glochidia. FMRFamide-like peptides have been identified in the central and peripheral nervous systems of various taxonomic groups of mollusks ( Price and Greenberg, 1977 ; Boer et al, 1980 ; Painter and Greenberg, 1982 ; Schot and Boer, 1982 ; Voronezhskaya et al, 2008 ; Dyachuk and Odintsova, 2009 ; Zatylny-Gaudin and Favrel, 2014 ; Battonyai et al, 2018 ; Yurchenko et al, 2019 ; Kotsyuba et al, 2020 ). The antiserum employed in this study was generated in rabbits against synthetic FMRFamide (Phe-Met-Arg-Phe-amide) conjugated to bovine thyroglobulin (Immunostar Incorporated; Cat.…”
Section: Methodsmentioning
confidence: 99%
“…20091). According to the published data, this antibody reacts with FMRFamide in various animals, including mollusks (gastropods, bivalves, and poyplacophorans) [136][137][138][139], indicating that the antigen has been conserved evolutionarily across a broad range of species. The manufacturer confirmed, specifically, that these antibodies react with antigens in caenogastropods, chitons, gastropods (Helix pomatia, Aplysia sp., Ilyanassa obsoleta, Lymnaea stagnalis, Mopalia muscosa, abalones), and bivalves (Mytilus trossulus).…”
Section: Antibodiesmentioning
confidence: 96%
“…The preadsorption of the diluted antiserum with 10 mg/mL BSA overnight at 4 • C did not influence this staining, indicating that these antibodies recognized only serotonin and not BSA. Previous data have shown that these antibodies detect serotonin in mollusks [135][136][137][138]. FMRFamide-like peptides were identified in the central and peripheral nervous systems of various taxonomic groups of mollusks [53][54][55]120,123,139].…”
Section: Antibodiesmentioning
confidence: 96%
See 1 more Smart Citation